Evaluation of the timing of using direct oral anticoagulants after ischemic stroke for patients with atrial fibrillation. Issue 3 (March 2023) - Yu, Hui-Tzu; Chen, Kuan-Hsuan; Lin, Chun-Jen; Hsu, Chia-Chen; Chang, Yuh-Lih
Abstract: Background and objective: Patients with atrial fibrillation (AF) are prescribed oral anticoagulants for stroke prevention; however, no evidence indicates that the use of direct oral anticoagulants (DOACs) in the first few days after ischemic stroke (IS) would result in favorable outcomes. This study evaluated the association between the timing of using DOACs after IS and their effectiveness and safety to determine the optimal timing. Methods: In this retrospective cohort study, we reviewed the electronic medical records of Taipei Veterans General Hospital. The 1-year outcomes of patients after DOAC initiation were evaluated. Different initiation time windows were compared (initiation time ≤3 days and >3 days in primary analysis). The primary composite outcome was stroke, transient ischemic attack, systemic embolism, or death due to IS. The primary safety outcome was major bleeding or clinically relevant nonmajor bleeding. The secondary composite outcome was all-cause mortality, thromboembolic event, or acute myocardial infarction/hemorrhagic events. Results: This study included 570 patients. The median initiation time of DOACs after IS in the patients with AF was 14 days. Compared the patients in whom DOACs were initiated after >3 days with those DOACs were initiated after ≤3 days, the adjusted hazard ratios (aHRs) of the primary composite outcome was 0.73 (95% confidence interval [CI]: 0.23–1.79), the aHR of primary safety outcome was 0.87 (95% CI: 0.34–1.90), and the aHR of secondary composite outcome was 0.65 (95% CI: 0.32–1.19). All the results were not statistically significant. In secondary analysis, we tested multiple time points of initiating DOACs. Compared with DOAC initiation after >14 days, the primary composite outcomes in the patients in whom DOACs were initiated ≤3, 4–7, and 8–14 days after IS were the same as the findings of the main analysis. After separating patients into different stroke severity groups, the results were similar to those in the main analysis. Conclusion: No significant association was observed between the timing of using DOACs and ischemic or hemorrhagic outcomes. The findings did not differ among different time points. Although we do not recommend avoiding the initiation of DOACs in the first few days after IS, we should consider that the early initiation of DOACs (≤3 days) would be appropriate only for patients who tend to experience thromboembolic events and have a low risk of bleeding. The optimal timing of initiation still must be confirmed by randomized controlled trials.